2014
DOI: 10.1590/s0103-84782014000100003
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of organic supplies for the egg parasitoid Telenomus podisi

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Similar results with the same organic products tested in this research were reported for Telenomus podisi (Hymenoptera; Platygastridae) (Silva;Bueno, 2014). In this context, it is important to emphasize that benefits of agricultural farming go beyond beneficial arthropod preservation.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results with the same organic products tested in this research were reported for Telenomus podisi (Hymenoptera; Platygastridae) (Silva;Bueno, 2014). In this context, it is important to emphasize that benefits of agricultural farming go beyond beneficial arthropod preservation.…”
Section: Discussionsupporting
confidence: 86%
“…These results are similar to those obtained with pupae of the parasitoid Telenomus remus (Nixon, 1937) (Hymenoptera: Platygastridae) when using commercial mixtures such as Borda-Ferti pH 7 (7% copper + 3.3% calcium) and Lime-sulfur mixture (20% sulfur + 10% quicklime), which were classified as slightly harmful (class 2) . Similarly, selective tests carried out by Silva and Bueno (2014), who used the commercial mixture Borda-Ferti pH 7 (7% copper + 3.3% calcium) in the pupal stage of Telenomus podisi (Ashmead, 1893) (Hymenoptera: Platygastridae), showed no RAE and was considered as harmless (class 1). Lime-sulfur mixture (20% sulfur + 10% quicklime) was tested in that experiment and showed to be harmless in all assessments, not causing a reduction in the adult emergence rate or changing the parasitism rate.…”
Section: Resultsmentioning
confidence: 99%
“…Products based on Baculovirus anticarsia, Bacillus thuringiensis, Azadirachtin-A, azadirachtin-B, nimbina and salamina, rotenoids, nitrogen, phosphorus and total organic carbon, sodium silicate, copper + calcium, and sulfur + quicklime exhibited low toxicity for pupae and adults of T. podisi. Therefore, these organic inputs can be used in soybean crops, as they do not compromise the potential of this parasitoid for controlling stink bugs [91].…”
Section: Pests Et(s) Referencementioning
confidence: 99%